Influence of Digital Technology & Data Analytics on Strategic Decision Making - Sutarman, Asep; Aprianto, Ronal; Adyatama, Rendhika; Yusup, Muhamad; Pokkali, Krishna Chaitanya (Startupreneur Business Digital (SABDA Journal), 2025)
In an increasingly advanced information age, digital technology and data analytics have become important pillars in effective decision making across a wide range of sectors. This journal aims to explore how digital technologies, including big data, artificial intelligence (AI), and machine learning, can be utilized to improve decision quality. Through a case study approach, we analyze several organizations that have successfully implemented these technologies in their decision making processes. The results show that the use of advanced data analytics enables organizations to unearth previously unreachable insights, improving the accuracy and speed of decision making. However, the research also identified several challenges, including the need for high analytical skills, data privacy concerns, and resistance to change in organizational culture. We found that to maximize the benefits of digital technologies, organizations need to adopt the right training strategies and create an environment that supports innovation. This research makes an important contribution to the understanding of how digital technologies can change the way organizations make decisions, as well as practical recommendations for more effective implementation. The findings are expected to help organizational leaders and decision-makers formulate better strategies to face the challenges and opportunities of the digital age. This study uniquely contributes by examining the synergistic interaction between digital technology and data analytics in strategic decision-making across multiple sectors. This study contributes by identifying key factors that influence the effectiveness of digital technology and data analytics adoption in strategic decision making and offering practical recommendations for companies to enhance the adoption of these technologies.